Data mining: foundations and intelligent paradigms : Volume 3: medical, health, social, biological and other applications - Jain, Lakhmi C.; Holmes, Dawn E. (Intelligent Systems Reference Library, 2012)
Data mining is one of the most rapidly growing research areas in computer science and statistics. In Volume 3 of this three volume series, we have brought together contributions from some of the most prestigious researchers in applied data mining. Areas of application covered are diverse and include healthcare and finance. Each of the chapters is self contained. Statisticians, applied scientists/ engineers and researchers in bioinformatics will find this volume valuable. Additionally, it provides a sourcebook for graduate students interested in the current direction of research in applied data mining.